PENGARUH INVESTASI, TENAGA KERJA DAN JUMLAH PENDUDUK TERHADAP PDRB SEKTOR PERTANIAN DI PROVINSI KALIMANTAN BARAT - B01111062, RANTO B01111062 BAGUS (Jurnal Pembangunan dan Pemerataan, 2017)
ABSTRACTThe purpose of this study is to analyze the "Effect Penananaman Domestic Investment, Foreign Investment, Total Labor and Population to the GDP of agriculture sector in the province of West Kalimantan". The data used in this research is time series data from 1989 to 2013 year. Penelititan method used is multiple regression analysis using a model of Ordinary Least Square (OLS) analysis tool Econometric Views (EViews) 8.Research shows that domestic investment, foreign investment, and the total population but not significant positive effect on the agricultural sector GDP, while total employment positive and significant impact on the agricultural sector GDP. The closeness of the relationship between the dependent variable and independent variables that affect the agricultural sector GDP West Kalimantan province amounted to 95,66 per cent which can be explained by four variables in the model. The remaining 4,34 percent is explained by other factors outside the model equations.Keywords: Domestic Investment, Foreign Investment, Total Labor, Population, and the agricultural sector GDP.